Pengaruh Viral Marketing dan Brand Awareness terhadap Niat Beli Merek Kopi Kenangan di Kota Surabaya - Venna Melinda Mulyaputri; Sanaji Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to examine the effect of viral marketing and brand awareness on consumer purchase intentions in the context of social media use, especially Instagram as a media marketer between companies and consumers, by providing information about the product. The sample used in this study amounted to 200 samples distributed online using Google Form. Data were analyzed using a simple linear regression method. Research results are the viral marketing and brand awareness variables positively affect buying intentions